Development of a Computer Interfacing Technique for the Study of Magnetic Forces of Superconductor and Permanent Magnet - Abas, Ariffin (2004)
The Computer together with the LABVIEW software can be used as automatic data acquisition system. The electronic balance with RS232 port is used for measuring the force exerted by the magnetic field strength. Knowledge of how to use DAQ PCI 6025E card combined with opto isolator chip RS307-064 are useful to amplifier 5V TTL signal from computer to 12V and make two stepper motors works with a step resolution of 0.08 mm and 0.009mm respectively. This project deals with the development of a computer interfacing technique for the study of magnetic forces of superconductor and permanent magnet, using the above system, which has been developed. It consists of two parts: the setting up of that automated experimental rig uses computer, together with the LABVIEW software, the electronic balance and the stepper motor and finally measuring the levitation force for the Bi1.6Pb0.4Sr2Ca2-xCdxCu3O10 system (where x=0.00(pure), x=0.02, x=0.05, x=0.07 and x=0.1) and magnetic forces for NdFeB permanent magnet. Graph of magnetic force as a function of distance were obtained. The magnetic force between two permanent magnets, NdFeB of different shapes and configurations were also studied. The Interactive LABVIEW Programming were developed so as to enable the calculation of either the repulsive or attractive forces between two cylindrical permanent magnets and the data are compared with the results obtained via experiment. Hysteresis loop were obtained for superconductor system, however it was not observed in the permanent magnet system. This phenomenon occurred in superconductor because it allows partial flux penetration in the vortex state, which are absents in the permanent magnet system. Magnetic forces for two permanent magnets obey the inverse square law of the distance between the two magnets, however it failed to describe the variation of levitation force as a function of distance for all superconductor samples. It was observed that the levitation force displayed exponential behavior, . The system that has been developed can be used as an affective teaching aid as it incorporates the interactive component.